2022
DOI: 10.7717/peerj.13693
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential anti-metastatic and antioxidative abilities of natural peptides derived from Tecoma stans (L.) Juss. ex Kunth in A549 cells

Abstract: Background Tecoma stans (L.) Juss. ex Kunth is a well-known medicinal plant found in tropical and subtropical regions. It contains a broad range of bioactive compounds that exhibit many biological effects, including antidiabetic, antibacterial, and antioxidative activities. However, the effect of natural peptides from T. stans against cancer progression and free radical production is unknown. This study aims to evaluate the cytotoxic, anti-metastatic, and antioxidative activities of natural peptides from T. st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Krobthong et al (2022) reported that cancer-promoting proteins, including CoA4, were downregulated in the natural peptides treated A549 lung cancer cells compared to the non-treated cells. The authors describe that natural peptides have anti-proliferative and anti-metastatic activities by suppressing cancer-promoting proteins and further reported that the anti-oxidative activity of natural peptides may be attributed to higher expression of ROS-reducing proteins [48]. This study indicates that CoA4 may be involved in ROS production.…”
Section: Biological Pathways and Protein-protein Interaction Analysismentioning
confidence: 74%
“…Krobthong et al (2022) reported that cancer-promoting proteins, including CoA4, were downregulated in the natural peptides treated A549 lung cancer cells compared to the non-treated cells. The authors describe that natural peptides have anti-proliferative and anti-metastatic activities by suppressing cancer-promoting proteins and further reported that the anti-oxidative activity of natural peptides may be attributed to higher expression of ROS-reducing proteins [48]. This study indicates that CoA4 may be involved in ROS production.…”
Section: Biological Pathways and Protein-protein Interaction Analysismentioning
confidence: 74%
“…In this case, nanoparticles are of interest due to their possible antitumor effect. Many studies have documented that biomolecules from plant extracts are useful for the formation of nanoparticles [66][67][68][69]. In this review, three articles were included in which the effectiveness of the extract and the nanoparticles were compared.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the PCA implementation from the decomposition module of scikit-learn was utilized [ 9 ]. The heatmap depicting phosphoprotein abundance was generated using the MultiExperiment Viewer (MeV) for SOTA clustering based on the expression data, following previously reported methods without any modifications [ 10 ].…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%